Self-report quality of life measure for people with schizophrenia: the SQLS. - Wilkinson, G; Hesdon, B; Wild, D; Cookson, R; Farina, C; Sharma, V; Fitzpatrick, R; Jenkinson, C (2000)
BACKGROUND: Quality of life is the subject of growing interest and investigation. AIMS: To develop and validate a short, self-report quality of life questionnaire (the Schizophrenia Quality of Life Scale, SQLS). METHOD: People with schizophrenia in Liverpool were recruited via the NHS. Items, generated from in-depth interviews, were developed into an 80-item self-report questionnaire. Data were factor analysed, and a shorter form measure was tested for reliability and validity. This measure was administered together with other self-report measures--SF-36, GHQ-12 and HADS--to assess validity. RESULTS: Data were analysed to produce a final 30-item questionnaire, comprising three scales ('psychosocial', 'motivation and energy', and 'symptoms and side-effects') addressing different SQLS dimensions. Internal consistency reliability of the scale was found to be satisfactory. There was a high level of association with relevant SF-36, GHQ-12 and HADS scores. CONCLUSIONS: The SQLS was completed within 5-10 minutes. It possesses internal reliability and construct validity, and promises to be a useful tool for the evaluation of new treatment regimes for people with schizophrenia.